The effect of systematic pediatric care on neonatal mortality and hospitalizations of infants born with oral clefts - Wehby George L; Castilla Eduardo E; Goco Norman; Rittler Monica; Cosentino Viviana; Javois Lorette; Kindem Mark; Chakraborty Hrishikesh; Dutra Graca; López-Camelo Jorge S; Orioli Iêda M; Murray Jeffrey C (BMC, 2011)
Abstract Background Cleft lip and/or palate (CL/P) increase mortality and morbidity risks for affected infants especially in less developed countries. This study aimed at assessing the effects of systematic pediatric care on neonatal mortality and hospitalizations of infants with cleft lip and/or palate (CL/P) in South America. Methods The intervention group included live-born infants with isolated or associated CL/P in 47 hospitals between 2003 and 2005. The control group included live-born infants with CL/P between 2001 and 2002 in the same hospitals. The intervention group received systematic pediatric care between the 7th and 28th day of life. The primary outcomes were mortality between the 7th and 28th day of life and hospitalization days in this period among survivors adjusted for relevant baseline covariates. Results There were no significant mortality differences between the intervention and control groups. However, surviving infants with associated CL/P in the intervention group had fewer hospitalization days by about six days compared to the associated control group. Conclusions Early systematic pediatric care may significantly reduce neonatal hospitalizations of infants with CL/P and additional birth defects in South America. Given the large healthcare and financial burden of CL/P on affected families and the relatively low cost of systematic pediatric care, improving access to such care may be a cost-effective public policy intervention. Trial Registration ClinicalTrials.gov: NCT00097149